2020
DOI: 10.1108/jima-12-2019-0256
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experience on behavioral intention for halal tourism

Abstract: Purpose The purpose of this paper is to examine halal certification for halal culinary, destination brand and emotional experiences on customer satisfaction and behavioral intention. Design/methodology/approach This study uses a quantitative survey approach to 400 respondents consisting of Muslim foreign and domestic tourists who had visited Lombok in the past three years. The sampling technique is by purposive sampling. The analysis technique used in this study is structural equation modeling-partial least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 25 publications
6
50
1
9
Order By: Relevance
“…Kotler and Keller (2016) defined customer behavior as a combination of mental, emotional and physical activities through which people choose, buy, use and determine to purchase products and services that meet their needs and desires. Understanding consumer behavior will facilitate management in efforts to develop products or services according to the needs and desires of consumers (Ratnasari et al , 2020a, 2020b, 2020c). Kim et al (2019) in Kim and Tang (2020) suggested that the starting point for exploring the new notion of customer behavior is to understand its precise composition or multi-dimensional nature.…”
Section: Introductionmentioning
confidence: 99%
“…Kotler and Keller (2016) defined customer behavior as a combination of mental, emotional and physical activities through which people choose, buy, use and determine to purchase products and services that meet their needs and desires. Understanding consumer behavior will facilitate management in efforts to develop products or services according to the needs and desires of consumers (Ratnasari et al , 2020a, 2020b, 2020c). Kim et al (2019) in Kim and Tang (2020) suggested that the starting point for exploring the new notion of customer behavior is to understand its precise composition or multi-dimensional nature.…”
Section: Introductionmentioning
confidence: 99%
“…Dari latar belakang masalah tersebut, penulis melakukan penelitian ini dengan tujuan untuk menganalisis seberapa besar potensi wilayah pantai di Kota Denpasar dapat menerapkan konsep halal beach tourism dengan analisis strategi menggunakan matriks SWOT. Konsep ini tidak berlaku hanya untuk wisatawan muslim saja, tapi juga berlaku untuk wisatawan umum baik wisatawan domestik maupun wisatawan mancanegara (Ratnasari, 2021). Manfaat dari penelitian ini untuk masyarakat yaitu supaya wisatawan mengetahui bahwa pantai di Kota Denpasar dapat dikunjungi oleh wisawatan muslim maupun wisatawan lainnya dengan sangat baik dan nyaman, sedangkan untuk pemerintah manfaatnya adalah untuk mengetahui bahwa pantai di Kota Denpasar dapat menjadi potensi kunjungan wisatawan muslim dan manfaat untuk peneliti adalah untuk mengetahui strategi analisis apa saja yang digunakan dalam menerapkan konsep halal beach tourism, serta manfaat untuk pelaku bisnis adalah untuk mengetahui strategi analisis apa yang digunakan dalam mengembangkan pariwisata di sekitar pantai Kota Denpasar.…”
Section: Pendahuluanunclassified
“…After creating a good environment of Halal tourism by domestic tourist then it will be much easier to promote Bangladesh as a halal tourist destination. Ratnasari et al, (2020) researched the emotional experience on the behavioral experiences and there they found that Halal certification of any food does not have any impact of customer satisfaction but it influences the behavioral intention of a customer and Shariff and Norenzayan (2011) conducted a research where they found People are more inclined to act in a virtuous or ethical way while they trust in frightening and punitive spiritual agents. Amat et al, (2014) conducted on research on 120 consumers on the perception towards purchasing halal food product where they found four factors which influence the perception of consumers and religious values are one of them.…”
Section: Religious Belief Affecting Tourist Behaviormentioning
confidence: 99%